2021
DOI: 10.3390/su13073645
|View full text |Cite
|
Sign up to set email alerts
|

Machine Learning Improvement of Streamflow Simulation by Utilizing Remote Sensing Data and Potential Application in Guiding Reservoir Operation

Abstract: Hydro-meteorological datasets are key components for understanding physical hydrological processes, but the scarcity of observational data hinders their potential application in poorly gauged regions. Satellite-retrieved and atmospheric reanalysis products exhibit considerable advantages in filling the spatial gaps in in-situ gauging networks and are thus forced to drive the physically lumped hydrological models for long-term streamflow simulation in data-sparse regions. As machine learning (ML)-based techniqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 51 publications
0
9
0
Order By: Relevance
“…For example, machine learning has been combined with near-real-time rainfall data from NASA's Tropical Rainfall Measuring Mission (TRMM) and soil moisture data from the National Oceanic and Atmospheric Administration's (NOAA's) Advanced Scatterometer (ASCAT) to simulate streamflow in India (Kumar et al, 2021). Machine learning with various satellite-derived hydrometeorological variables has also been used to calculate streamflow in the Hanjiang River in China (He et al, 2021). Data assimilation, another approach to data fusion, has also improved land surface model predictions of water storage, particularly when multiple satellite data products are combined (Khaki et al, 2020).…”
Section: Hydropower and Water Supplymentioning
confidence: 99%
“…For example, machine learning has been combined with near-real-time rainfall data from NASA's Tropical Rainfall Measuring Mission (TRMM) and soil moisture data from the National Oceanic and Atmospheric Administration's (NOAA's) Advanced Scatterometer (ASCAT) to simulate streamflow in India (Kumar et al, 2021). Machine learning with various satellite-derived hydrometeorological variables has also been used to calculate streamflow in the Hanjiang River in China (He et al, 2021). Data assimilation, another approach to data fusion, has also improved land surface model predictions of water storage, particularly when multiple satellite data products are combined (Khaki et al, 2020).…”
Section: Hydropower and Water Supplymentioning
confidence: 99%
“…However, it should be noted that the reservoir water balance in reality is more complex due to the contribution of precipitation and evaporation over the reservoir surface (as previously indicated in Chapter 1; Equation (1.1)). Some previous studies found that the meteorological variables played a more important role in ML model performance than timing information (e.g., Zhang et al, 2019;He et al, 2021). Other studies stated that meteorological variables had an insignificant influence on ML model performance, as they were already captured by the timing information, and thus could be neglected (e.g., Yang et al, 2016).…”
Section: Available Data To Reflect Real-time Reservoir Operationmentioning
confidence: 99%
“…On the other hand, it can be argued that the addition of Q t−1 can essentially account for the operators' decisions on a daily basis, which have been the main issue in real-time reservoir operation modelling for a long time. Several studies have applied the Q t−1 input and achieved excellent ML model performance (e.g., Chen et al, 2018;Zhang et al, 2018aZhang et al, , 2019He et al, 2021;Hong et al, 2021). In reality, however, using the Q t−1 input is only logical and useful when the Q t−1 data are obtained from prediction instead of observations, considering that the observed Q t−1 data are not available in the case of multi-day outflow forecasting.…”
Section: Effects Of Selected Input Variables On Model Performancementioning
confidence: 99%
See 2 more Smart Citations